ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PETANI TEMBAKAU DI DUSUN MENCEH DESA MENCEH KECAMATAN SAKRE TIMUR KABUPATEN LOMBOK TIMUR - SURIADI, AHMAD; MAYADASARI, ELITA (Ganec Swara, 2025)
This research aims to determine the influence of factors on the income of tobacco farmers in Menceh Hamlet, Menceh Village, Sakre District, East Lombok Regency. This study uses a quantitative approach, data analysis using multiple linear regression, data collection techniques used are observation, questionnaires and literature studies. The population in this study were all tobacco farmers in Menceh Hamlet, Menceh Village. The sampling technique in this study used judgmental sampling. Researchers took 40 tobacco farmers randomly from 300 populations. The results of the study revealed that Land Area (X1) did not have a significant effect on the income (Y) of tobacco farmers in Menceh Hamlet, Menceh Village. This is evidenced by the T-value for the Land Area variable (X1) which is -0.657 smaller than the T-table value of 2.028 and with a significant value of 0.007 greater than 0.05. The Amount of Capital (X2) does not have a significant effect on the income (Y) of tobacco farmers in Menceh Hamlet, Menceh Village, this is evidenced by the T-value for the Capital Amount variable (X2) which is -0.555 smaller than the T-table of 2.028 and with a significant value of 0.582 greater than 0.05. Labor (X3) has a significant effect on the income (Y) of tobacco farmers in Menceh Hamlet, Menceh Village, this is evidenced by the T-value for the Capital Amount variable (X2) which is 4.885 greater than the T-table value of 2.028 and with a significant value of 0.000 less than 0.05. The variables Land Area, Capital Amount, and Labor simultaneously affect the level of income. This is proven by the results of the F-test which produces a calculated F value of 7.770 which is greater than the T table of 2.87